Washed Microbiota Transplantation Lowers Blood Pressure in Patients With Hypertension - Zhong, Hao-Jie; Zeng, Hong-Lie; Cai, Ying-Li; Zhuang, Yu-Pei; Liou, Yu-Ligh; Wu, Qingping; He, Xing-Xiang (Frontiers in Cellular and Infection Microbiology, 2021)
Background Although transplantation of the fecal microbiota from normotensive donors has been shown to have an antihypertensive effect in hypertensive animal models, its effect on blood pressure in patients with hypertension is unclear. This study aimed to assess the effect of washed microbiota transplantation (WMT) from normotensive donors on blood pressure regulation in hypertensive patients. Methods The clinical data of consecutive patients treated with washed microbiota transplantation (WMT) were collected retrospectively. The blood pressures of hypertensive patients before and after WMT were compared. The factors influencing the antihypertensive effect of WMT in hypertensive patients and fecal microbial composition of donors and hypertensive patients were also analyzed. Results WMT exhibited an antihypertensive effect on blood pressure: the blood pressure at hospital discharge was significantly lower than that at hospital admission (change in systolic blood pressure: −5.09 ± 15.51, P = 0.009; change in diastolic blood pressure: −7.74 ± 10.42, P < 0.001). Hypertensive patients who underwent WMT via the lower gastrointestinal tract (β = −8.308, standard error = 3.856, P = 0.036) and those not taking antihypertensive drugs (β = −8.969, standard error = 4.256, P = 0.040) had a greater decrease in systolic blood pressure, and hypertensive patients not taking antihypertensive drugs also had a greater decrease in diastolic blood pressure (β = −8.637, standard error = 2.861, P = 0.004). After WMT, the Shannon Diversity Index was higher in six of eight hypertensive patients and the microbial composition of post-WMT samples tended to be closer to that of donor samples. Conclusion WMT had a blood pressure-lowering effect in hypertensive patients, especially in those who underwent WMT via the lower gastrointestinal tract and in those not taking antihypertensive drugs. Therefore, modulation of the gut microbiota by WMT may offer a novel approach for hypertension treatment.